PERBEDAAN PERSEPSI TENTANG KARIER DI KANTOR AKUNTAN PUBLIK ANTARA MAHASISWA DAN STAF KANTOR AKUNTAN PUBLIK - Kurnia Kurnia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
The objective of this study is to examine the perception differences about a career in accounting firms between students and staffs in public accounting. It was hypothesized that there was a significant difference between student expectations about career in accounting firms and the experiences of CPA firm professionals. The survey was conducted to collect information on the differences between the job expectations of accounting students and the actual work experiences of accounting staff. To evaluate the differences between the two groups, t-tests was performed.The results indicate few significant differences between accounting students and accountant staff’ perceptions. Students expectations were higher than accountants staff experiences for almost every questions. These differences between expectations and experiences may cause employee dissatisfaction, increased turnover rate or the loss of quality people in the accounting profession. Some approaches could be taken to eliminate at least some of the differences between student perceptions and accountant staff experiences. One approach would be communicated more accurately to students the realities of the current public accounting environment. The other approach would begin changing the public accounting environment in ways that can attract the best and brightest students to chose accounting profession.